The Development of Clinical Nursing Practice Guideline for Prevention and Reduction of Hypersensitivity Reaction Severity in Breast Cancer Patients undergoing Chemotherapy Taxane Regimen - Wangchai, Warunee; Pain, Krisanee; Kaewintah, Yupawan; Tikaew, Nittaya; Kongmun, Juralak; Daoprasert, Karnchana; Phongphanngam, Sutthida (Journal of The Department of Medical Services, 2024)
Background: Hypersensitivity reaction is an important risk to monitor in cancer patients undergoing chemotherapy. Patients should receive proper and timely assessment and management of hypersensitivity reaction to ensure their safety. Objective: This study aimed to develop a clinical nursing practice guideline (CNPG) for the prevention and reduction of hypersensitivity severity in breast cancer patients receiving Taxane chemotherapy. Method: The study applied the clinical practice guideline development model of National Health and Medical Research Council of Australia 1999 and the Department of Nursing at Chulalongkorn Hospital Thai Red Cross Society in 2019. Collecting empirical evidence and assessing the level of credibility, comprising 29 research studies and 4 related guidelines, a total of 33 topics were extracted to develop evidence-based nursing practices. The CNPG was developed through a review process by 4 experts. The overall score on the AGREE II assessment form was 87.2 and was revised to ensure appropriateness. The CNPG was then trialed with 2 sample groups: 10 nurses’ chemotherapy and 31 breast cancer patients receiving taxane chemotherapy. Results: The synthesis of the results for creating CNPG included the following components: 1) Patient care before receiving chemotherapy by assessing readiness to receive chemotherapy and risk factors for hypersensitivity, 2) Patient care during chemotherapy, including drug administration methods, premedication, surveillance for signs and symptoms, and managing hypersensitivity reactions, and 3) Post-chemotherapy patient care, including assessing complications and providing advice and guidance. When trialed with a sample group was found that expressed satisfaction level was high in the nurse’s group (mean = 4.10, SD = 0.32). The highest level of satisfaction was clarity and the ability to practicality (mean = 4.60, SD = 0.52). While hypersensitivity severity was found in 1 patient (3.2%), mild (grade 2) severity, which could be resolved and continued chemotherapy. Conclusion: The CNPG should be implemented throughout the organization.